Texting slang: Misinterpretation in communication / Suriyati Ujang, Norhidayah Md Yusof and Hanani Mohamed Hamdan - Ujang, Suriyati; Md Yusof, Norhidayah; Mohamed Hamdan, Hanani (Universiti Teknologi MARA Cawangan Kedah, 2018)
Texting slang is defined as a language that is commonly used in messaging as a medium of an interaction among people. However, this language does not include emoticons. The examples of texting slang are LOL, ROFL, TTYL, etc. Texting slang is highly recognized as a language that is used by users on social media. However, miscommunication and misunderstanding are bounded to be happened to those who are new to the culture or certain groups. The objectives for this research are to check the proportion of users’ current knowledge in texting slang and to identify the relationship between knowledge of texting slang and misinterpretation. The study was conducted in a public university in the east coast of Malaysia, to see if texting slang is widely used among students and staff in this institution. During the survey, questionnaire was distributed in the campus in order to collect the data. The data collected using stratified sampling with the total of 335 respondents out of 2765 total population. Based on the findings, in terms of the users’ knowledge in texting slang, the results for the interpretation of the abbreviations and acronyms show that not all respondents know what the actual meaning of each abbreviation and acronym that were used. Next, it can be seen that there is a significant relationship between the knowledge of texting slang creates the misinterpretation of the text content among users. Thus, further research in terms of the users’ knowledge and misinterpretation regarding texting slang and how these two elements affect in users’ communication whether written and spoken, could be carried out in order to understand texting slang better and thoroughly.